Legal provision of information security process of provision electronic administrative services - Shevchuk, Oksana; Kuz, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The statistic analyzes the provisions of the normative legal acts, as well as depicts the official system of looking at the information security process of providing information services. It is necessary to establish the need for additional development and to formulate one step before the information security is secured, as a complex straightforward It also analyzes the genesis of scientific glances at the information security mechanism of providing administrative services. Doslіdzheno day because of the safety and information security of the process of providing administrative services in the minds of a fraudulent conflict. At the current level of Ukraine, the administrative reform in the sphere of electronic regulation and the provision of administrative services to switch to the electronic format has been successfully implemented. According to the Law of Administrative Services in electronic form, one can expect from one state web portal of electronic services, including through the integrated information systems and state bodies of the self-government. The presence of a potently functional electronic control is a high indicator of the power of a state before the state’s informational support and is the main instrument of the stabilization of the system of providing administrative services. Having learned about the reports of the Organizational Organizations of the United Nations "E-Government Survey 2020", [4] in the rating of the countries, as a high level of development of electronic regulation, our state took the 69th month of 2018, showing the positive for 13 positions. The specifics of the given polling in the sub-powers of the Chotiri group: from low, middle, high and even higher levels of development of electronic regulation. Ukraine has become one of the powers that may be in a high level of development of electronic regulation. The author comes before the weekend, but there are three important straightforward information security services provided to the community in electronic form. The use of a secure information environment means the transition to general methodological approaches to information security in the field of information systems